Klaudiusz Elian o nazwach cykad - Kaczyńska, Elwira; Witczak, Krzysztof Tomasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
In his work Περὶ ζῴων ἰδιότητος (De natura animalium X 44) Claudius Aelian describes cicadas’ names in the following way: „There are, it seems, many species of cicada (τέττιξ), and those who are skilled in these matters enumerate them and report their names. Thus, the Ashen one (τεφράς) is so called from its colour; whence the Membrax (μέμβραξ) got its name I do not know; and Chirper (λακέτας), it appears, is the name for a cicada; and I have heard tell of the Long-tail (κερκώπη) and the Shriller (ἀχέτας) and the Prickly one (ἀκάνθιος). Well, these are all the kinds of Cicada of which I remember having heard the names, but if anyone has got to know more than those that I have mentioned, he must tell them” (translated by Scholfield 1959: 339–341). It is necessary to follow Aelian’s suggestion and explain all the mentioned cicadas’ names from the point of view of the Greek etymology and word-formation.